Knowledge and utilization of obstetric ultrasound and associated factors among pregnant mother in Africa: a systematic review and meta-analysis - Gashaw, Anteneh; Figa, Zerihun; Abebe, Yonas; Demeke, Abel Desalegn; Sime, Yohanes (The Ultrasound Journal, 2025)
Background: Obstetric ultrasound (US) is a non-invasive imaging method that employs sound waves to explore the abdominal and pelvic areas of a pregnant woman. It is recommended to have at least two ultrasound scans during pregnancy, one in the first trimester and another in the second trimester, to identify potential complications and improve perinatal outcomes. While this practice is widely implemented in developed nations, its utilization in many African countries remains suboptimal. This systematic review and meta-analysis aims to examine the level of knowledge and utilization of obstetric ultrasound among pregnant women in Africa, providing insights into its awareness and utilization across the continent.Method: A systematic review and meta-analysis were conducted following PRISMA guidelines. Extensive literature searches were carried out across various databases, including PubMed, Google Scholar, ScienceDirect, Web of Science, Scopus, and African Online Journal databases. The pooled prevalence was estimated using a weighted inverse variance random-effects model. Heterogeneity among studies was assessed using the Cochrane Q-test and I 2 statistics, while publication bias was evaluated through a funnel plot and Egger’s test. Stata v17 software was employed to analyze factors associated with the utilization of obstetric ultrasound among pregnant women in Africa.Result: A total of 622 articles were initially identified, with 23 ultimately meeting the inclusion criteria for this review, including five studies that addressed both knowledge and utilization of obstetric ultrasound. The overall knowledge level among pregnant women in Africa regarding obstetric ultrasound was estimated at 74.33% (95% CI 63.27–85.38%), while the pooled proportion of utilization was 63.3% (95% CI 51.59–75.02%). Subgroup analysis revealed that both knowledge and utilization levels were highest in Western Africa, whereas knowledge was lowest among pregnant women in Eastern Africa. Pregnant women with good knowledge of obstetric ultrasound were significantly more likely to utilize the service, with a pooled odds ratio (POR) of 8.41 (95% CI 4.66–12.16).Conclusion: This systematic review and meta-analysis revealed a moderate utilization of obstetric ultrasound among pregnant mothers in Africa, with an increasing trend over time, particularly after 2020. The overall level of knowledge about obstetric ultrasound among mothers was 74.33%, and knowledge was identified as the key factor significantly associated with ultrasound utilization.